FepR as a Central Genetic Target in the Adaptation to Quaternary Ammonium Compounds and Cross-Resistance to Ciprofloxacin in Listeria monocytogenes - Douarre, Pierre-Emmanuel; Sévellec, Yann; Le Grandois, Patricia; Soumet, Christophe; Bridier, Arnaud; Roussel, Sophie (Frontiers in Microbiology, 2022)
The foodborne pathogen, Listeria monocytogenes, (Lm), frequently undergoes selection pressure associated with the extensive use of disinfectants, such as quaternary ammonium compounds, which are widely used in food processing plants. The repeated exposure to sub-inhibitory biocide concentrations can induce increased tolerance to these compounds, but can also trigger the development of antibiotic resistance, and both increase the risk of food contamination and persistence in food production environments. Although the acquisition of genes can explain biocide tolerance, the genetic mechanisms underlying the adaptive cross-resistance to antibiotics remain unclear. We previously showed that repeated exposure to benzalkonium chloride (BC) and didecyldimethyl ammonium chloride (DDAC) led to reduced susceptibility to ciprofloxacin in Lm strains from diverse sources. Here, we compared the genomes of 16 biocide-adapted and 10 parental strains to identify the molecular mechanisms of fluoroquinolone cross-resistance. A core genome SNP analysis identified various mutations in the transcriptional regulator fepR (lmo2088) for 94% of the adapted strains and mutations in other effectors at a lower frequency. FepR is a local repressor of the MATE fluoroquinolone efflux pump FepA. The impact of the mutations on the structure and function of the protein was assessed by performing in silico prediction and protein homology modeling. Our results show that 75% of the missense mutations observed in fepR are located in the HTH domain of the protein, within the DNA interaction site. These mutations are predicted to reduce the activity of the regulator, leading to the overexpression of the efflux pump responsible for the ciprofloxacin-enhanced resistance.